Late mortality reduction among survivors of germ cell tumors in childhood and adolescence in Europe: A report from the PanCareSurFup cohort. Issue 12 (2nd October 2022) - Trama, Annalisa; Bernasconi, Alice; Botta, Laura; Byrne, Julianne; Grabow, Desiree; Reulen, Raoul C.; Calaminus, Gabriele; Terenziani, Monica
Abstract: Background: Data on late mortality from pediatric germ cell tumors (GCTs) are limited to small case series. Our population‐based study aimed to investigate excess risk of death in survivors of GCT in childhood and adolescence, whether long‐term mortality changed over time and by period of diagnosis. Methods: The PanCare Childhood and Adolescent Cancer Survivor Care and Follow‐Up Studies (PanCareSurFup) cohort includes 2773 five‐year survivors diagnosed under 21 years of age with gonadal and extragonadal GCT (from 1940 to 2008). We calculated standardized mortality ratios (SMRs) and absolute excess risks (AERs). We fitted a Cox's model to assess the impact of treatment period. We estimated 10‐year survival and calculated average percentage changes between periods of diagnosis (1970–1979, 1980–1989, 1990–1999) to assess whether late mortality decreased. Results: GCT survivors had an almost four‐fold excess risk of dying compared to general population. The risk of death for patients treated after 1980 was nearly halved compared to patients treated before 1980. Survivors diagnosed in 1990–1999 had a 10‐year survival rate of 99%, which was 2.4% and 1.1% higher than for patients treated in 1970–1979 and 1980–1989, respectively. Conclusions: This is the largest population‐based study in Europe and showed a decrease in long‐term mortality for survivors of GCTs in childhood and adolescence over the last decades. After the introduction of platinum compound in 1980, which is a paradigm of success compared to the previous treatments, no major changes in drug therapies have been made to treat GCTs in the last 40 years. However, GCT survivors maintain an excessive risk of death that requires long‐term care.